Assessment of national policy to promote corporate governance in Nepal (Quest Journal of Management and Social Sciences, 2019)
Background: Corporate governance, or good governance may have a direct impact not only on economic health of an organization, but also the overall status of national governance or systems administration. By now, Nepal has succeeded to attain political stability and attainment of policy stability is in its making. It is right time for all type of organizations to institute favorable traditions, customs, policies, rules and regulations with increased level of accountability to help the nation with right policy direction. Therefore, reviewing the Nepalese corporate governance scenario by assessing governing policies, prevailing issues, challenges and practices deem necessary.Objectives: The main purpose of this paper was to establish an assessment of national policy effectiveness on corporate governance, specifically in the banking sector.Methods: Fully based on desk review performed in a qualitative setting of inquiry.Results: There is closer linkage between legal and regulatory provisions and effectiveness of corporate governance in the Nepalese banking sector.Conclusions: For an emerging economies, improving the level of corporate governance can serve a number of important public policy objectives such as reducing market vulnerability to financial crises, controlling transaction costs and cost of capital, and resulting with investor confidence and capital market development situation.Implications: Nepal needs timely review and updates in not only policies governing bank and financial institutions, but also the entire company’s act of the country to make all type of organizations accountable and transparent in their operations to win the investor confidence and market trust.